1990
DOI: 10.1128/jvi.64.5.2082-2089.1990
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a major DNA-binding domain in the herpes simplex virus type 1 DNA-binding protein (ICP8)

Abstract: We have studied the major DNA-binding protein (ICP8) from herpes simplex virus type 1 to identify its DNA-binding site. Since we obtained our protein from a cell line carrying multiple chromosomally located copies of the ICP8 gene, we first analyzed this protein to assess its similarity to the corresponding viral protein. Our protein resembled the viral protein by molecular weight, response to antibody, preference for binding single-stranded DNA, and ability to lower the melting temperature of poly(dA-dT). To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
18
0

Year Published

1996
1996
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(19 citation statements)
references
References 63 publications
(52 reference statements)
1
18
0
Order By: Relevance
“…As shown in Fig. 8, the cysteine modified at position 254 lies outside the centrally located DNA-binding domain which has been identified by other studies (16,19,35,55) and well outside a minimal DNA-binding domain (residues 563 to 636) recently identified in our laboratory (unpublished data). Thus, at least two regions of the protein are involved in different aspects of the interaction of ICP8 with singlestranded DNA, with the central region most likely being involved in intrinsic binding and the region around residue 254 being involved in cooperative binding.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…As shown in Fig. 8, the cysteine modified at position 254 lies outside the centrally located DNA-binding domain which has been identified by other studies (16,19,35,55) and well outside a minimal DNA-binding domain (residues 563 to 636) recently identified in our laboratory (unpublished data). Thus, at least two regions of the protein are involved in different aspects of the interaction of ICP8 with singlestranded DNA, with the central region most likely being involved in intrinsic binding and the region around residue 254 being involved in cooperative binding.…”
Section: Discussionsupporting
confidence: 64%
“…These interactions, however, are considerably weaker than those observed with single-stranded DNA. The presence of ICP8 destabilizes poly(dA)-poly(dT) duplexes (55), and it has been shown that ICP8 is capable of displacing short oligonucleotides annealed to long single strands of DNA (2). Finally, ICP8 has been shown to aid in the annealing of separated DNA strands under the proper conditions (13).…”
mentioning
confidence: 99%
“…Basic and aromatic amino acids of DNA-binding proteins are thought to participate in interaction with DNA substrates. BmNPV DBP contains a motif, K 18 -R 21 -Y 33 -F 41 -Y 53 -R 64 -W 71 -K 80 , which presents a perfect match to the consensus sequence, K/RX 2-5 K/RX 4-12 F/YX 2-14 F/YX 6-13 F/YX 1-19 K/RX 3-26 F/Y/WX 6-11 R/K, found in all SSB proteins from prokaryotic and eukaryotic organisms (38) Isolation of a novel baculovirus DNA-binding protein, Bm-NPV DBP, poses intriguing question about the possible function of this protein in virus replication. Its preferential binding to ssDNA (Fig.…”
Section: Discussionmentioning
confidence: 89%
“…Although SSBs do not have a high degree of primary sequence similarity, there are common sequence motifs that have emerged from comparative analyses. A domain containing conserved aromatic and charged residues thought to mediate DNA binding is present in many SSBs and appears to be present in the I3 protein as well (11,34,51) (Fig. 11A).…”
Section: Discussionmentioning
confidence: 99%